2019
DOI: 10.1002/ghg.1858
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to simulated carbon capture and storage (CCS) CO2 pipeline leakage: the effect of soil type

Abstract: Carbon capture and storage (CCS) has been proposed as a bridging technology to enable the transition to an energy system based on renewable sources. Many high CO2‐emitting industries (such as the power industry) are distant from potential carbon storage sites (such as offshore geological reservoirs) and an infrastructure of CO2 transportation must therefore be developed to carry the CO2 to safe storage. As such there is a need to understand the risks involved and the mitigation of potential leaks associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In 2010, 68% of global GHG emissions were contributed by energy usage, which includes 90% CO 2 and 9% CH 4 , N 2 O and other gases . Combustion of fossil fuel has been observed to hasten the long‐term carbon cycle, injecting carbon into the atmosphere and causing anthropogenic climatic changes …”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, 68% of global GHG emissions were contributed by energy usage, which includes 90% CO 2 and 9% CH 4 , N 2 O and other gases . Combustion of fossil fuel has been observed to hasten the long‐term carbon cycle, injecting carbon into the atmosphere and causing anthropogenic climatic changes …”
Section: Overview Of Sectorial Ghg Emissions In Pakistanmentioning
confidence: 99%
“…42 Combustion of fossil fuel has been observed to hasten the long-term carbon cycle, injecting carbon into the atmosphere and causing anthropogenic climatic changes. 43 Previous studies have examined impact of energy on climate change through adopting various econometric approaches, including time series data analysis, and concluded that energy consumption is the main contributor of CO 2 emissions in the environment which causes the change in climate. [26][27][28][29][30] The same case was witnessed in Pakistan where the energy sector contributed over half of the total GHG emissions.…”
Section: Overview Of Sectorial Ghg Emissions In Pakistan Ghg Emissionmentioning
confidence: 99%
“…Pipeline wrapping and routine gas seal test is applied to prevent such leakage (Xiuzhang, 2014). Serious impact on unadaptable plant species and microorganisms were reported due to CO 2 infiltration along CCS transport line (Rastelli et al, 2015;Lake and Lomax, 2019). The best solution for reducing the transportation cost and minimising the hazard risk is to select the nearest storage location from the capturing site.…”
Section: Transporting the Captured Comentioning
confidence: 99%
“…The average atmospheric CO2 concentration had increased from 280 ppm in industrial era to 411 ppm in May 2019 (Dlugokencky and Tans, 2019;Lake and Lomax, 2019). The average CO2 concentration is increasing continuously by more than 2 ppm/year (Metz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%